HUBUNGAN PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) TERHADAP BERAT BADAN ANAK USIA 6-24 BULAN - Suriani " Pratiwi; Juniar " Ernawaty; Siti " Rahmalia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractThis study aim to determine the relationship of complementary feeding (MP-ASI) against the weight of children aged 6-24 months in Puskesmas Harapan Raya Pekanbaru. Design in this research was descriptive correlation with cross sectional approach. Samples were 77 respondents taken based on inclusion criteria using proportionate stratified random sampling. The  instrument used was a questionnaire that was tested it’s validity and reliability. Univariate analysis used to determine the frequency distribution and bivariate using chi-square test. This study showes that administration of complementary feeding (MP-ASI) is good as many as 47 respondents (61,0%), not good 30 respondents (39,0%) in the provision of complementary feeding (MP-ASI). This study also indicates that is 60 infant with normal weight (77,9%), and 17 infant with not normal weight (22,1%). From Chi Square analysiz, it is indicate that the p value (0,000) < α (0,05), that means that there is a significant relationship between. The provision of complementary feeding (MP-ASI) toward weight of children aged 6-24 months in Puskesmas Harapan Raya Pekanbaru. According to this research, it is expected that parents could give complementary feeding to their child, that appropriate to their age therefore will incrase their children’s weight in normal range.Keywords: Weight, complementary feeding (MP-ASI)